Skeletal muscle glycogen content at rest and during endurance exercise in humans: A meta-analysis - Areta, J. L.; Hopkins, W. G. (Sports Medicine, 2018)
Skeletal muscle glycogen is an important energy source for muscle contraction and a key regulator of metabolic responses to exercise. Manipulation of muscle glycogen is therefore a strategy to improve performance in competitions and potentially adaptation to training. However, assessing muscle glycogen in the field is impractical, and there are no normative values for glycogen concentration at rest and during exercise. Objective: The objective of this study was to meta-analyse the effects of fitness, acute dietary carbohydrate (CHO) availability and other factors on muscle glycogen concentration at rest and during exercise of different durations and intensities. Data Source and Study Selection